Exopolysaccharides from microalgae: production, characterization, optimization and techno-economic assessment - Kocer, Anil Tevfik; Inan, Benan; Kaptan Usul, Sedef; Ozcimen, Didem; Yilmaz, Mustafa Tahsin; Isildak, Ibrahim (SPRINGER, 2021)
Microalgae cultivation for exopolysaccharide production has getting more attention as a result of their high hydrocarbon biosynthesis skill. The aim of this study is to examine the exopolysaccharide production potential of different species of microalgae. In this context, exopolysaccharides were produced from Chlorella minutissima, Chlorella sorokiniana and Botryococcus braunii microalgae and the effects of carbon and nitrogen content in the growth medium and illumination time on exopolysaccharide production were analyzed statistically using Box-Behnken experimental design. In addition, techno-economic assessment of exopolysaccharide production were also performed by using the most productive microalgae and optimum conditions determined in this study. As a result of the experiments, it was seen that C. minutissima, C. sorokiniana and B. braunii produced 0.245 +/- 0.0025 g/L, 0.163 +/- 0.0016 g/L and 0.117 +/- 0.0007 g/L exopolysaccharide, respectively. Statistically, it was observed that there was an inverse relationship between the exopolysaccharide production and investigated parameters such as illumination period and carbon and nitrogen amounts of culture mediums. The techno-economic assessment comprising microalgal exopolysaccharide (EPS) bioprocess was carried out, and it showed that the system can be considered economically viable, yet can be improved with biorefinery approach.
Keywords: Exopolysaccharide; Microalgae; Bioprocess; Chlorella minutissima; Chlorella sorokiniana; Botryococcus braunii; EXTRACELLULAR POLYSACCHARIDE; BOTRYOCOCCUS-BRAUNII; CHLORELLA-SOROKINIANA; GREEN MICROALGA; CELL-GROWTH; LIFE-CYCLE; STRAIN; ALGAE; KEFIR; PURIFICATION; Microbiology